Penentuan Arah Kiblat Menggunakan Azimuth Bintang Gienah (Studi Pengamatan Langit Di Desa Bonto Bulaeng, Kecamatan Sinoa, Kabupaten Bantaeng, Sulawesi Selatan - Rahmawati; Agus, Jasdar (Universitas Islam Negeri Alauddin Makassar, 2024)
The main issue in this research is the determination of the Qibla direction using the azimuth of the Gienah star in Bonto Bulaeng Village, Sinoa Subdistrict, Bantaeng Regency, South Sulawesi. This study highlights the use of stars as a guide in determining the Qibla direction and evaluates the accuracy of star azimuth in the process. This research is a qualitative field study, where the researcher conducts direct observation of the study object. The Qibla direction is determined using the azimuth reference of the Gienah star with azimuth data calculated beforehand, through a Shari'a and astronomical approach using qualitative methods. The data collection methods employed include observation and documentation. The results of the study indicate that the azimuth of the Gienah star can be used as an alternative in determining the Qibla direction, especially at night when the Qibla direction cannot be determined directly. The implication of this research is that the star azimuth method is one way to determine the Qibla direction. Additionally, other celestial objects with measurable azimuth can also be used. The author hopes this study will expand the understanding of Qibla direction measurement using star objects. The use of star azimuth should only be considered as an alternative in determining the Qibla direction and is not recommended for beginners in the field of falak and astronomy, due to the risk of star misidentification that can lead to inaccuracy.